Thermal design of air cooled condenser of a solar adsorption refrigerator - Rouag, Amar; Benchabane, Adel; Labed, Adnane; Boultif, Nora (Journal of Applied Engineering Science & Technology, 2016)
The objective of this paper is to study the design of a condenser of a solar adsorption refrigerator which will be tested in the region of Biskra (Algeria). The LMTD (log mean temperature difference) method is used to calculate the size of the condenser applying experimental data obtained from the literature. For this purpose, a calculation code has been developed to determine the total heat transfer area of the heat exchanger. Therefore, we present a comparison between calculated and experimental results obtained from the literature. This comparison allowed the validation of the calculation method by applying the same experimental conditions. The discussion of the results indicates that we cannot use the ambient air in free convection mode as a cooling fluid if its temperature exceeds 30°C. This problem presents the greatest obstacle especially in the Saharan regions, such as in Biskra, where the average ambient air temperature during the summer exceeds 35°C. As a solution, we propose in this article the improvement of the heat transfer by the air-forced convection mode. Thus, it is established that the use of the air fan can extend the operating temperature limits of the condenser above 35°C.
Keywords: Solar adsorption refrigerator; Condenser; LMTD; Sizing; Free convection; Forced convection